2018
DOI: 10.1111/radm.12344
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of competence specialization in the effect of external R&D on innovative performance

Abstract: This paper studies the functional specialization of SMEs' technological competence and its moderating role in the effect of external R&D on their innovative performance. Technological competence consists of many functional dimensions such as basic research, product architecture, process construction, testing, and evaluation, which constitute a sequence of innovation tasks. The specialization of technological competence allows SMEs to utilize economies of specialization in R&D, enhance their bargaining power an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…However, with the passage of time during which innovation became a key organisational success factor among strong competition and globalisation (Anwar, 2018;Clauss, 2017;Clauss et al, 2020), scholars felt the need for RBV when it came to the aspects of innovative performance and its outcomes (Anwar, 2018;Memon et al, 2020). Several studies as a result tested the role of tangible and intangible resources in the innovative performance of firms (Garcia Martinez et al, 2017;Hock-Doepgen et al, 2021;Koo & Lee, 2019).…”
Section: New Venturesmentioning
confidence: 99%
“…However, with the passage of time during which innovation became a key organisational success factor among strong competition and globalisation (Anwar, 2018;Clauss, 2017;Clauss et al, 2020), scholars felt the need for RBV when it came to the aspects of innovative performance and its outcomes (Anwar, 2018;Memon et al, 2020). Several studies as a result tested the role of tangible and intangible resources in the innovative performance of firms (Garcia Martinez et al, 2017;Hock-Doepgen et al, 2021;Koo & Lee, 2019).…”
Section: New Venturesmentioning
confidence: 99%
“…Regardless of what happens to the stripped stars and gas, LCBGs have long been proposed as the progenitors of lower-mass galaxies once their current burst of star formation has faded (Guzman et al 1996;Koo et al 1997). The local-group, dE galaxy NGC 205 is often cited as a possible descendant of LCBGs.…”
Section: Lcbgs As Progenitors Of Dwarf Ellipticalsmentioning
confidence: 99%
“…Other than very early work by Koo et al (1997) confirming their presence in clusters, relatively few studies have targeted the cluster LCBG population; however, recent observations have indicated that the cluster environment is triggering the LCBG phase (Crawford et al 2006(Crawford et al , 2011. In fact, their kinematic and spatial distributions suggest that LCBGs represent galaxies experiencing initial infall into galaxy clusters (Crawford et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chandler and Hanks (1994) state that a leader's competence moderates the relationship between the learning opportunities provided by the organisation and IWB. Koo and Lee (2018) are of the view that competence has a positive moderating role between the relationship of LWB displayed in external R&D project and innovative performance. Lastly, in the context of the high-tech industry of telecommunication, our findings suggest that leader technical competence has a significant strengthening effect on the positive relationship between LWB and IWB when both leaders LSTC SRLTC are high.…”
Section: Iwbmentioning
confidence: 99%